Usage analysis of print and online journals of the U.P. College of Medicine Library and its implications to periodical subscriptions - Canceran, Gina G. (2011)
Usage analysis is a technique for understanding the usage statistics of something, for example the web statistics of a website or the statistics of usage of online journals. The study focused only on the periodical subscriptions of the Medical Library for the period 2009-2010 both print and online subscription. It covered the year 2009-2010 in measuring the usage.